Effect of melting temperature on dimensional accuracy in sand casting product - Ahmad Faizal, Mohamad (2009)
This study is conducted based on the needs to find accurate method for sand casting in producing the clamping vise. Vise is well known as for clamping the work piece. This study is carried out to investigate effect of temperature on dimensional accuracy (mm) of the finish product using sand casting and to find the optimum melting temperature of aluminum for sand casting process. Different setting of melting temperature is applied for sand casting process which is 660°C, 720°C and 780°C. These temperatures are taken using infra red (IR) thermometer. Final products are measured using vernier caliper with tolerance (±0.03 mm) respectively. The data obtained are analyzed using standard analysis method and graph is plotted for graphical analysis purpose. The result showed that melting temperature 720°C has better dimensional accuracy rather than melting temperature 660°C and 720°C. From the analysis, it showed that every different setting of melting temperature influenced the performance of final parts in terms of dimensional accuracy (mm).